Pengaruh Arus Kas, Profitabilitas dan Ukuran Perusahaan Terhadap Financial Distress (Studi Kasus Pada Perusahaan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2018 – 2020) - Suci Apriyani; Solihin Sidik; Rina Maria Hendriyani (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2024)
This study aims to determine the effect of cash flow, profitability, and firm size on Financial Distress. The research method used is a quantitative descriptive and verification approach. The sample taken consisted of 45 Real Estate companies with annual financial statements.Based on the analysis of research data, the following conclusions are obtained: (1) cash flow has no effect on financial distress (2) Profitability has a positive and significant effect on financial distress (3) Company size has a negative and significant effect on financial distress.